ESSENTIAL FEATURES OF EFFECTIVE ACADEMIC WRITING IN ENGLISH - Yu.V. Lysanets; O.M. Bieliaieva; L.B. Slipchenko; K.H. Havrylieva; H.Yu. Morokhovets (Проблеми екології та медицини)
The article discusses the features of academic writing in English based on the recommendations from the British Council in Ukraine in the framework of the “Researcher Connect” project, aiming to facilitate the transition to academic standards of English and improve the academic discourse produced by non-native language users. The authors outline major tendencies in the modern English language as pertains to written discourse and provide recommendations for rendering academic writing persuasive. It is a well-established fact that academic writing in English possesses unique features, which must be respected and taken into account. Hence, a transfer of academic norms from a person's mother tongue to English can be a challenge, which may impair the quality of academic writing. Presenting the research results without consideration of academic norms, grammar, and lexical features of English academic writing can lead to mistakes and misunderstanding, and result in a written work of poor quality, even if the research findings are valid. The mechanisms of improving the academic writing skills during the study of English for Academic Communication with due account for relevant grammar and lexical peculiarities have been explored. Therefore, the major challenge for researchers is the difficulty in transition to academic standards of a foreign language. The article discusses the surface and the deeper purposes in any academic writing; the significance of understanding one’s audience; the concepts of persuasion, clarity, and conciseness, as well as grammar and lexical means for achieving them. Developing the communication skills of Ukrainian scientists is crucial for successful international communication and cooperation. The study of potential difficulties, which the Ukrainian medical professionals may face in the process of academic writing in English, is important for developing the guidelines to eliminate possible mistakes and avoid misunderstanding in a medical setting. Further study of the peculiarities of academic writing in English will contribute to the optimization of international professional communication, the expansion of inter-institutional dialogue, and the integration of Ukraine into the world community.